Advanced Materials for Energy and Environmental Applications - Park, Sunghoon (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Advanced materials for energy and environmental applications (such as rapid heating, anti-fouling/anti-virus surface, chemical sensor, textile/stretchable sensor, fuel cell, and lithium-ion batteries) have been extensively investigated in the academic and industrial fields. The advent of cabon-based nano-materials (carbon nanotubes, graphene, and carbon black) and inonganic nano-materials (Ag wire/particles, Cu mesh, and transition metal dichalcogenide) has accelerated research interest in energy and environmental applications. This book is focused on the emerging concept and improvement of energy and environmental basic research, as well as in the characterization and analysis of novel energy and environmental base materials. The contents of the book are as below: - Theoretical and experimental studies on advanced conducting nanocomposites; - Electrical properties of nanocomposites under various conditions (dynamic mode, aspect ratio, alignment, and contents) and its applications; - Advanced material for energy applications; - Analysis and materials for environmental applications.